Diseño de los sistemas de agua potable y alcantarillado Sanitario para el recinto del CIRUELO de la parroquia San Carlos del Canton Naranjal, provincia del Guayas - Yamunaque Preciado, Javier Miguel (2015)
The Citadel Santa Fe first stage of the canton Arenillas province of El Oro, lacks a network of drinking water, sanitary sewer and storm, so this becomes a serious problem for the residents of the sector and jeopardizes the health of population. Objective arises Perform the study and design of the whole system of Drinking Water, Sewerage and Stormwater in Ciudadela Santa Fe First Stage of Canton Arenillas El Oro Province, in 2014. The methodology used was based on research (field visits, survey, consultation books, publications, internet), description (current basic services) and analysis (description) thanks to three processes indicated could be obtained results research, since that is where the essence of the inquiry results used to have conclusions and recommendations to the problems presented and to raise the best approach is. The proposal is based on the minimum standards set by the Health Standards "STANDARD ECUATORIANO Building Code" also hosts several criteria cited authors in the project. Design area is 21.65 ha., With a population of 2167 inhabitants for a return period of 25 years. The distribution network Water has a length of 9228.87 m, PVC material structured wall, the maximum pressure of the network is m.c.a 40.40 and a minimum pressure of 37,35m.c.a. Network Sewerage system has a length of 2741.52 m, with 33 wells and 597 review cases for review. Network Storm Sewer System has a length of 2536.95 m, with 37 and 103 wells review sinks.